Isolation and characterization of Escherichia coli pantothenate permease (panF) mutants. - Vallari, D S (1985)
Mutants of Escherichia coli K-12 defective in the pantothenate permease (panF) were isolated and characterized. The panF mutation resulted in the complete loss of pantothenate uptake and of the ability to use extracellular vitamin for growth. The growth phenotypes of panF panD, panF panB, and panF panC double mutants showed that the cytoplasmic membrane was impermeable to external pantothenate. Analysis of the intracellular and extracellular metabolites from strain DV1 (panF panD) labeled with beta-[3-3H]alanine demonstrated that a carrier-mediated mechanism for efficient pantothenate efflux remained in the panF mutant. Genetic mapping of this nonselectable allele was facilitated by the isolation of three independent Tn10 insertions close to panF. Two- and three-factor crosses located panF at minute 72 of the E. coli chromosome and established the gene order fabE panF aroE.